Bti sprays do not adversely affect non‐target aquatic invertebrates in French Atlantic coastal wetlands. Issue 1 (20th September 2013) - Lagadic, Laurent; Roucaute, Marc; Caquet, Thierry; Arnott, Shelley
Summary Both the increase in human mobility and climate change contribute to the globalization of vector‐borne diseases. Some mosquito species are efficient disease vectors in Europe, thus increasing the risk of epidemic (re)emergence. Bacillus thuringiensis var. israelensis (Bti) is considered as the most efficient larvicide to control mosquito populations with negligible environmental impacts. However, repeated field applications of Bti over many years raise the question of possible long‐term effects on non‐target invertebrates with putative subsequent alterations of food webs. Environmental effects of Bti have mainly been studied in continental freshwater wetlands. Much less is known for brackish water coastal wetlands. We investigated whether repeated treatments with Bti, applied as VectoBac® WG over seven consecutive years, may affect non‐target invertebrate communities in wetlands of the French Atlantic coast. Particular attention was devoted to invertebrates potentially used as food sources by shorebirds and wading birds. Invertebrates were sampled in the water and sediment of control and VectoBac®‐treated saltmarsh pools between 2006 and 2012. Taxa abundance data were used to calculate community descriptors and to analyse the potential structural changes due to VectoBac® using the principal response curve method and similarity analysis. Physicochemical parameters were measured in the same pools so that homogeneity of the environmental conditions between the control and treated areas could be tested. We demonstrated that long‐term use of VectoBac® WG in French Atlantic coastal wetlands had no influence on the temporal evolution of the taxonomic structure and taxa abundance of non‐target aquatic invertebrate communities, which is highly driven by abiotic factors. In addition, over the long term, the amount of invertebrates that could be used as food resources by birds is maintained in VectoBac®‐treated areas. Synthesis and applications. Reduced application rate and targeted spraying of VectoBac® WG in mosquito breeding sites minimize potential environmental impacts of Bacillus thuringiensis var. israelensis (Bti). Even so, surveillance of its possible primary side effects is needed, which requires comparable control and treated areas. Indeed, systematic temporal trends and subtle differences in the range of variation of abiotic factors result in discrepancies between control and treated area in terms of invertebrate abundance, which could be wrongly attributed to VectoBac®. Management decisions and mitigation measures may therefore benefit from (i) extending surveillance to a time frame that allows for coverage of the immense temporal variation in taxa abundance and diversity and (ii) the inclusion of environmental variables in the monitoring of non‐target animal communities potentially exposed to Bti.